Pengenaan Sanksi Adat Bagi Pelaku Tindak Pidana Penyalahgunaan Wewenang Terhadap Keuangan Pada Lembaga Perkreditan Desa (LPD) Tuwed Kecamatan Melaya Kabupaten Jembrana - Kadek Mas Aditya Mahottama; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
Abuse of authority in customary village institutions is not only sanctioned by national law but also sanctioned by customary law or commonly called awig – awig. For example: the abuse of authority that occurred in the Village Credit Institution (LPD) Tuwed, Melaya District, Jembrana Regency. This research was conducted to examine the form of imposition of customary sanctions for perpetrators of criminal acts of abuse of authority over finances at the Tuwed Village Credit Institution (LPD) Melaya District, Jembrana Regency. The research method used in this research is empirical legal research by approaching people who can be used as sources. Sources of data used in this research are primary and secondary data. Data were analyzed using qualitative analysis methods. The results in this research are: The existence of customary law in the national legal system is still gray until now because in several cases that occurre which should have involved customary law or customary village awig - awig but during the settlement process it seemed that it had no power or ignored in court proceedings and national law. And the abuse of authority over finances at the Tuwed Village Credit Institution for the settlement of criminal cases through customary law consists of the first, the mediation system, and second, the restorative justice system and the sanctions given based on customary law in the form of social sanctions.